PXDN as a pan-cancer biomarker and promotes tumor progress via immune inhibition in nasopharyngeal carcinoma - Li, Yu-Chun; Xiao, Yan-Hong; Chen, Fei-Xiong; Xiao, Si-Yu; Lin, Jian-Mei; Cai, Shu-Tao; Zeng, Cui-Lan; Ye, Xue-Yan; Yu, Xu-Fa; Yuan, Li; Li, Shi-Bing (Frontiers in Oncology, 2024)
BackgroundInvestigating oncogenes and the mechanisms driving oncogenic processes in human tumors is imperative for the development of efficient therapies. Peroxidasin (PXDN) has been reported to play a critical role in tissue development and homeostasis. However, the role of PXDN in the occurrence and development of Nasopharyngeal Carcinoma (NPC) remains unknown.MethodsData from multiple databases, including GEO and TCGA, were used to analyze the expression levels of PXDN. Taking nasopharyngeal carcinoma as an example, in vitro experiments were conducted to explore the biological functions of PXDN. Overexpression of stable cell lines was achieved through lentiviral infection, cell proliferation was examined using CCK8 and BrdU incorporation assays, and clone formation experiments were performed to assess cell growth. Transwell and wound healing assays were employed to evaluate cell invasion and migration abilities. Additionally, immunofluorescence staining with multiple targets was used to analyze the immune microenvironment of the tumor tissues. Co-culture experiments, followed by clone formation and CFSE incorporation assays, were conducted to observe the impact of NPC stable cell lines on T cells. Flow cytometry was performed to detect surface markers and cytokines in T cells after co-culture to assess T cell function.ResultsPXDN was highly expressed in multiple tumors, and its high expression and mutation profile were correlated with poor survival. Functionally, PXDN plays a crucial role in promoting oncogenic processes by enhancing NPC cell proliferation and metastasis. Mechanistically, PXDN activates extracellular matrix (ECM) signaling pathways while simultaneously inhibiting T-cell infiltration and activation, thereby facilitating cancer progression.ConclusionWe characterized PXDN as a valuable biomarker for pan-cancer diagnosis and prognosis. We also uncovered new oncogenic roles for PXDN in promoting cancer progression and regulating T-cell immunosuppressive function in NPC.